Study on the Impact Mitigation Effect of Artificial Rock Backfill Layers for Submarine Pipelines Based on Physical Model Tests and Numerical Simulations - Guixi Jiang; Long Yu; Yunrui Han; Chunhong Hu; Dayong Zhang; Qing Yang (Oceans, 2025)
Submarine pipelines laid across navigational channels are highly susceptible to anchor drop impacts, which can cause deformation and disrupt normal pipeline operations. In severe cases, anchor impacts may lead to oil and gas leaks, resulting in significant economic losses and environmental damage. To ensure the safe operation of submarine pipelines, artificial rock backfilling is widely employed as a protective measure. Compared with complex pipeline protection structures, this approach is both cost-effective and efficient. In the physical model experiment, a combination of total force sensors and thin-film sensors was used to measure the dynamic response of pipelines under anchor impact. Additionally, The FEM-DEM numerical method was used to simulate the dynamic response and interaction process of anchor impact on the rock protection layer and pipeline. Numerical results were compared with experimental data to analyze the effects of rock protection layer thickness, backfill rock particle size, and pipeline sublayer types on pipeline impact response. The results show a good agreement between the physical model tests and numerical simulation studies, revealing several factors that influence the mitigation effect of the rock protection layer. This study provides a valuable scientific reference for the installation of rock protection layers for pipelines.